Losing ground : environmental stress and world food prospects - Eckholm, Erik P. (New York : Norton, 1976)
Current discussion of the environmental crisis often centers on the pollution problems of the industrial world. The author calls for massive tree-planting campaigns, agricultural reforms to benefit peasant farmers, and a slowdown in world population growth. He predicts that, unless there is a major shift in global political priorities, a third of mankind will become mired in hopeless destitution, a tragedy with ominous implications for world order.
Includes bibliographical references: p. [203]-219 and index.
oif 28/01/2019
Loans
Keywords: Agricultural ecology; Agriculture; Nature--Effect of human beings on; Food supply; Soil erosion